Application of nanofiber carriers for sampling of microbial biomass from contaminated groundwater - Nechanická, Magda; Dolinová, Iva; Špánek, Roman; Tomešová, Denisa; Dvořák, Lukáš (The Science of the total environment, 2021)
Sampling of microbial biomass is crucial for understanding and controlling remediation processes ongoing at contaminated sites in general, particularly when molecular genetic analyses are employed. In this study, fiber-based carriers with a nanofiber layer were developed and tested as a method to sample microbial biomass in groundwater for molecular genetic analysis. Nanofiber carriers, varying in the shape and the linear density of nanofibers, were examined throughout a 27-month monitoring period in groundwater contaminated with benzene, toluene, ethylbenzene and xylene isomers (BTEX), and chlorinated ethenes. The effect of carrier shape and nanofiber layer density on the microbial surface colonization and composition of the microbial biofilm was determined using real-time PCR and next-generation sequencing (NGS) analysis. Differences in microbial community composition between nanofiber carriers, groundwater, and soil samples were also analyzed to assess the applicability of carriers for biomass sampling at contaminated sites. The nanofiber carriers showed their applicability as a sampling tool, particularly because of their easy manipulation that facilitates DNA isolation. The majority of taxa (Proteobacteria, Firmicutes, and Bacteroidetes) present on the carrier surfaces were also detected in the groundwater. Moreover, the microbial community on all nanofiber carriers reflected the changes in the chemical composition of groundwater. Although the carrier characteristics (shape, nanofiber layer) did not substantially influence the microbial community on the carrier surface, the circular and planar carriers with a nanofiber layer displayed faster microbial surface colonization. However, the circular carrier was the most suitable for biomass sampling in groundwater because of its high contact area and because it does not require pre-treatment prior to DNA extraction.
Keywords: chemické látky znečišťující vodu; Nanofibers; podzemní voda; nanovlákna; Groundwater; Biomass sampling; Biodegradation, Environmental; Next-generation sequencing; biodegradace; biomasa; Real-time PCR; Biomass; Biomass carrier; Water Pollutants, Chemical